Deletion of the 2-acyl-glycerophosphoethanolamine cycle improve glucose metabolism in Escherichia coli strains employed for overproduction of aromatic compounds. Issue 1 (December 2015) - Aguilar, César; Flores, Noemí; Riveros-McKay, Fernando; Sahonero-Canavesi, Diana; Carmona, Susy; Geiger, Otto; Escalante, Adelfo; Bolívar, Francisco
Abstract Background As a metabolic engineering tool, an adaptive laboratory evolution (ALE) experiment was performed to increase the specific growth rate (µ) in anEscherichia coli strain lacking PTS, originally engineered to increase the availability of intracellular phosphoenolpyruvate and redirect to the aromatic biosynthesis pathway. As result, several evolved strains increased their growth fitness on glucose as the only carbon source. Two of these clones isolated at 120 and 200 h during the experiment, increased their μ by 338 and 373 %, respectively, compared to the predecessor PB11 strain. The genome sequence and analysis of the genetic changes of these two strains (PB12 and PB13) allowed for the identification of a novel strategy to enhance carbon utilization to overcome the absence of the major glucose transport system. Results Genome sequencing data of evolved strains revealed the deletion of chromosomal region of 10, 328 pb and two punctual non-synonymous mutations in thedhaM andglpT genes, which occurred prior to their divergence during the early stages of the evolutionary process. Deleted genes related to increased fitness in the evolved strains arerppH, aas, lplT andgalR . Furthermore, the loss ofmutH, which was also lost during the deletion event, caused a 200-fold increase in the mutation rate. Conclusions During the ALE experiment, both PB12 and PB13 strains lost thegalR andrppH genes, allowing the utilization of an alternative glucose transport system and allowed enhanced mRNA half-life of many genes involved in the glycolytic pathway resulting in an increment in the μ of these derivatives. Finally, we demonstrated the deletion of theaas -lplT operon, which codes for the main components of the phosphatidylethanolamine turnover metabolism increased the further fitness and glucose uptake in these evolved strains by stimulating the phospholipid degradation pathway. This is an alternative mechanism to its regeneration from 2-acyl-glycerophosphoethanolamine, whose utilization improved carbon metabolism likely by the elimination of a futile cycle under certain metabolic conditions. The origin and widespread occurrence of a mutated population during the ALE indicates a strong stress condition present in strains lacking PTS and the plasticity of this bacterium that allows it to overcome hostile conditions.